Optimal Synthesis and Evaluation of Tri-Amine Modified Ordered Mesoporous Carbon (TriFeOMC) and Its Application for the Adsorption of Arsenic and Lead From Aqueous Solution - Khan, Hafiz Osama Sarwar; Zhu, Jianzhong; Jalil, Abdul; Sarwar, Rana Talha; Hameed, Fazli; Xu, Feifie (Frontiers in Materials, 2020)
Heavy metal pollution has become a serious problem due to increasing industrial waste, causing damage to water ecological environment, economic development and human health through their toxic effects. A unique Triamine-Iron-ordered mesoporous carbon (TriFeOMC) material was produced via a soft template approach. The ensuing sample of TriFeOMC was tested for the adsorption of arsenic (As) and Lead (Pb) along with its comparison with other two materials, which are Ordered mesoporous carbon (OMC) and Iron-ordered mesoporous carbon (FeOMC). The adsorption efficiency of TriFeOMC was excellent (92%) for the adsorption of As whereas, OMC has shown higher efficiency (88%) for the adsorption of Pb. The interaction between amino group and acidic groups on the surface of carbon formed a strong layer during Pb ions adsorption process, which resulted decreased adsorption of Pb on TriFeOMC. The Freundlich model described the adsorption isotherms in an efficient way for all materials in the present study. The results of adsorption kinetics were complex because TriFeOMC along with FeOMC followed nearly similar fit for both pseudo models for the adsorption of As, whereas, the adsorption results of Pb were described well using the pseudo-second-order model. The OMC adsorption dynamics showed a good fit with the pseudo-second-order model for both heavy metals. The novel material TriFeOMC with large pore volume and large surface area showed excellent results for the adsorption of arsenic from the aqueous solution. The results show the highest efficiency of TriFeOMC for adsorption of arsenic from arsenic-polluted water due to higher adsorption capacity with total pore volume 1.70 nm to 300.00 nm along with highly suitable pore width of 0.0680 cm³/g for adsorption, and therefore, it is highly recommended to use TriFeOMC for the adsorption of arsenic from polluted water.